STABILITY OF INDONESIA'S SECTORAL EMPLOYMENT OPPORTUNITIES AMIDST FDI AND THE COVID-19 PANDEMIC - Dudi Duta Akbar, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study analyzes the impact of Covid-19 and Foreign Direct Investment, how this affects the level of employment in Indonesia and captures Indonesia's role in the global economic recovery. This study uses panel data with eight cross sections and a time series from 2017–2021, with the dependent variable the level of employment opportunity and the independent variables are FDI, real GDP, real wages and Covid- 19 as a dummy variable. This study found that the level of employment opportunity had no effect on the Covid-19 period. The independent variables in this study did not significantly affect the level of employment opportunities. This shows that the economic impact caused by a pandemic is different from war, which does not involve the destruction of capital, rather the death rate in the productive segment of the population, and Indonesia is not affected by this. The lack of effect of the pandemic outbreak on job opportunities and FDI shows that Indonesia is part of the Global Value Chain (GVCs) and Indonesia can suppress investor concerns about the outbreak. The next finding is that the growth in the economic sector in the Covid-19 period was not significant, followed by the level of job opportunities in each of these economic sectors.